The Double-Edged Sword: Social Media’s Impact on Press Freedom and Democratic Information Flows in Diverse Asian Contexts - Juned, Sulaiman (MD Research Center, 2025)
This article examines the controversy surrounding press freedom in Asia, focusing on the influence of social media on the democratization of information in Asian countries. Press freedom in Asia faces significant challenges from both political pressure and government control over traditional media. In the digital age, social media has become the primary platform for information sharing; however, it also presents new challenges related to the spread of inaccurate information and restrictions on freedom of expression. This study employs a literature review method to analyze relevant works concerning the relationship between social media, press freedom, and the democratization of information across various Asian countries. The findings indicate that while social media has the potential to expand democratic space, its impact on press freedom is heavily influenced by government policies and local socio-political conditions. In some countries, social media is used to advocate for free speech and amplify opposition voices, whereas in others, it serves as a government tool to limit the flow of information deemed harmful. The article further highlights the challenges Asian countries face in balancing information freedom and social media regulation to prevent misinformation. The study concludes that social media plays a crucial role in advancing press freedom, but its success depends on wise management and appropriate regulation.